Linguistic Structuring in the Heritage Text: “Al-Khansa’s Tragedy” as a Model - laouidji, Ahmed (El Omda in Linguistics and Discourse Analysis, 2025)
Modern linguistic courses are featured by the emergence of a number of modern technologies and mechanisms, which allow researchers to access, investigate, and read any linguistic activity from various aspects, according to different visions and multiple approaches, which may enable researchers to check and analyze the linguistic styles used in these texts –whether prose or poetry- and disclose their meaning. Since linguistic morphology is one of these styles developed in the world of linguistic and literary studies to reveal the hidden secrets of linguistic, psychological, stylistic and semantic texts, which may be the direct reason that pushed the writer to follow this writing style. Therefore, what is the truth about this mechanism –linguistic morphology-? How can morphology contribute to the construction of the literary text? What are its manifestations in poetry text?